Chromatin as alarmins in necrotizing enterocolitis - Nofi, Colleen P.; Prince, Jose M.; Wang, Ping; Aziz, Monowar (Frontiers in Immunology, 2024)
Necrotizing enterocolitis (NEC) is a severe gastrointestinal disease primarily affecting premature neonates, marked by poorly understood pro-inflammatory signaling cascades. Recent advancements have shed light on a subset of endogenous molecular patterns, termed chromatinassociated molecular patterns (CAMPs), which belong to the broader category of damageassociated molecular patterns (DAMPs). CAMPs play a crucial role in recognizing pattern recognition receptors and orchestrating inflammatory responses. This review focuses into the realm of CAMPs, highlighting key players such as extracellular cold-inducible RNA-binding protein (eCIRP), high mobility group box 1 (HMGB1), cell-free DNA, neutrophil extracellular traps (NETs), histones, and extracellular RNA. These intrinsic molecules, often perceived as foreign, have the potential to trigger immune signaling pathways, thus contributing to NEC pathogenesis. In this review, we unravel the current understanding of the involvement of CAMPs in both preclinical and clinical NEC scenarios. We also focus on elucidating the downstream signaling pathways activated by these molecular patterns, providing insights into the mechanisms that drive inflammation in NEC. Moreover, we scrutinize the landscape of targeted therapeutic approaches, aiming to mitigate the impact of tissue damage in NEC. This in-depth exploration offers a comprehensive overview of the role of CAMPs in NEC, bridging the gap between preclinical and clinical insights.